Influence temperature to Flavonoid stability of palm sugar ( Arenga pinnata Merr .) as antioxidant: english - Hadi, Samsul; Aulia Ramadani, Rizka; Rahmadina, Nazwa; Qadry Sukmana, M. Laily; Nastiti, Kunti (Institute Of Computer Science (IOCS), 2024)
Palm sugar is the resulting liquid from flower tree sugar palm (Arenga pinnata Merr . ) through a thickening process . One of Content main are Flavonoids as antioxidant . Research purposes This is set flavonoid levels in various type temperature making brown sugar . Method used in study This is AlCl3 that is formation complex color on difference temperature in making palm sugar . Temperature used in study This is 55; 65; 75; 85; 100 0 C. Materials used is roomie palm oil , methanol , AlCl 3 , potassium acetate and equipment used is spectrophotometer. Accuracy results Flavonoid levels in sugar processing at a temperature of 55 0 C were obtained flavonoid content 1.72 ± 0.013; at a temperature of 65 0 C is 2.46 ± 0.023; at 75 0 C 1.32 ± 0.031; at a temperature of 85 0 C 1.18 ± 0.012; at 100 0 C 0.88 ± 0.012 mg QE/g sugar. Research conclusions This based on determination flavonoid levels in the process of making brown sugar, then along with increase temperature can make sugar lower Flavonoid levels in brown sugar